Computational analysis identifies druggable mutations in human rBAT mediated Cystinuria. Issue 14 (22nd September 2021) - Pandey, Bharati; Aarthy, Murali; Sharma, Mahima; Singh, Sanjeev Kumar; Kumar, Vinay
Abstract: Culex quinquefasciatus Cqm1 protein acts as the receptor for Lysinibacillus sphaericus mosquito-larvicidal binary (BinAB) toxin that is used worldwide for mosquito control. We found amino acid transporter protein, rBAT, as phylogenetically closest Cqm1 homolog in humans. The present study reveals large evolutionary distance between Cqm1 and rBAT, and rBAT ectodomain lacks the sequence motif which serves as binding-site for the BinAB toxin. Thus, BinAB toxin can be expected to remain safe for humans. rBAT (heavy subunit; SLC3A1 ) and catalytic b 0, + AT (light subunit; SLC7A9 ), linked by single disulfide bond, mediate renal reabsorption of cystine and dibasic amino acids in Na + independent manner. Mutations in rBAT cause type I Cystinuria disease which shows global prevalence, and rBAT can be thought as an important pharmacological target. However, 3D structures of rBAT and b 0, + AT, the two components of b 0, + heteromeric amino acid transporter systems, are not available. We constructed a reliable homology model of rBAT using Cqm1 coordinates and that of transmembrane b 0, + AT subunit using LAT1 coordinates. Mapping of pathogenic mutations onto rBAT ectodomain revealed their scattered distribution throughout the rBAT protein. Further, our computational simulations-based scoring of several known deleterious mutations of rBAT revealed that mutations those do not compromise the protein fold and stability, are localized on the same face of the molecule. These residues are expected to interact with the b 0, + AT transporter. The present study thus identifies druggable sites on rBAT that could be targeted for the treatment of type I Cystinuria. Communicated by Ramaswamy H. Sarma